2020
DOI: 10.3389/fchem.2020.00544
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Porous Graphene–Iron Carbide Hybrid Derived From Functionalized Graphene-Based Metal–Organic Gel as Efficient Electrochemical Dopamine Sensor

Abstract: A metal-organic gel (MOG) similar in constitution to MIL-100 (Fe) but containing a lower connectivity ligand (5-aminoisophthalate) was integrated with an isophthalate functionalized graphene (IG). The IG acted as a structure-directing templating agent, which also induced conductivity of the material. The MOG@IG was pyrolyzed at 600 • C to obtain MGH-600, a hybrid of Fe/Fe 3 C/FeO x enveloped by graphene. MGH-600 shows a hierarchical pore structure, with micropores of 1.1 nm and a mesopore distribution between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…54 Lastly, a gel formed from Fe(NO 3 ) 3 Á6H 2 O and 5amino isophthalic acid in the presence of isophthalic acid functionalized graphene, however it was not possible to activate the pore space of this gel. 55 In another example, a Hybrid MOG was developed by the group of Tapas Maji, where the synthesis of hydrogel was achieved by electrostatic interactions between negatively charged LAPONITE s nanoclay discs and positively charged ZIF-8 nanoparticles. 56 Further, this hydrogel was utilized as a drug delivery system by preparing the hydrogel using 5fluorouracil loaded ZIF-8 particles.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…54 Lastly, a gel formed from Fe(NO 3 ) 3 Á6H 2 O and 5amino isophthalic acid in the presence of isophthalic acid functionalized graphene, however it was not possible to activate the pore space of this gel. 55 In another example, a Hybrid MOG was developed by the group of Tapas Maji, where the synthesis of hydrogel was achieved by electrostatic interactions between negatively charged LAPONITE s nanoclay discs and positively charged ZIF-8 nanoparticles. 56 Further, this hydrogel was utilized as a drug delivery system by preparing the hydrogel using 5fluorouracil loaded ZIF-8 particles.…”
Section: Methodsmentioning
confidence: 99%
“…54 Lastly, a gel formed from Fe(NO 3 ) 3 ·6H 2 O and 5-amino isophthalic acid in the presence of isophthalic acid functionalized graphene, however it was not possible to activate the pore space of this gel. 55…”
Section: Metal–organic Gelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have reported the application of 2D conducting MOF and MOF hybrid-based materials for energy storage applications . There have been reports on MOF derived materials including metal oxides, heteroatom-doped (nitrogen, boron) nanoporous carbon materials, metal sulfides/phosphides, and layered double hydroxides. , These MOF derived materials showed potential in electrochemical applications owing to their large surface area, significant pore volume, and controlled morphologies, with a degree of tunability of redox active sites . As discussed earlier, some of the MXene/MOF derived composites were fabricated by three different strategies.…”
Section: Mxene/mof Derived Compositesmentioning
confidence: 99%
“…Carbon cloth (CC) has become an attractive conductive substrate in recent years as a result of its outstanding flexibility, ultrahigh conductivity, low cost, and easy cutting, and its interlaced fibers are beneficial to the modification and growth of various functional materials . Among the nanomaterials providing improved sensitivity and operating performance, 3D graphene walls (GWs) fabricated by plasma-enhanced chemical vapor deposition (PECVD) to form a 3D maze structure has attracted increasing attention in the application of electrochemical biosensing and cell adhesion/growth platform, benefiting from its high specific surface area, good mechanical strength, free-standing architecture, and good biocompatible properties. Compared to 2D graphene sheets (GSs), 3D GWs can immensely reduce the accumulation of GSs via the strong π–π interaction and intersheet contact resistance, which can facilitate the modification of catalytic materials, reduce the repulsive force, and enhance the mass transport between negatively charged graphene and H 2 O 2 . ,, Unfortunately, electrochemical direct oxidation or reduction of H 2 O 2 frequently requires a relatively high overpotential, resulting in susceptibility to the effects of interfering substances coexisting in biological fluids, which also require high overpotential. To overcome the above problems, the combination of graphene and various metal nanocatalysts was used to improve the performance of biosensing, including Au nanoparticles (Au NPs), NiO nanomaterials, Fe 3 O 4 QDs, Pt nanoparticles (Pt NPs), etc.…”
Section: Introductionmentioning
confidence: 99%